Glasovna terapija Lee Silverman predstavitev in uporaba - Drljepan, Mateja (Rehabilitacija (Ljubljana), 2017)
The Lee Silverman voice treatment is an evidence-based treatment approach primarily intended for patients with hypokinetic dysarthria. This condition is most frequently encountered in patients with Parkinson's disease (PD). With the progress of the disease, PD patients start talking with a weaker and quieter voice, which makes it increasingly hard for others to understand them. Due to the disordered perception of their own speech, the patients are not aware that they speak much more quietly. They often report that their family members are having hearing difficulties, and that their own speech is of normal volume. Barely intelligible speech is the main reason for the referral to a speech language therapist. The Lee Silverman voice treatment, which is aimed at improving speech volume and consequently improving speech intelligibility, has turned out to be the most suitable speech therapy method to improve the speech of PD patients. This high-intensity treatment helps patients recognise that their voice is too weak and teaches them to speak louder, while still remaining within the normal volume range, in order to improve their speech intelligibility. With training, the patients are able to increase the volume of their speech quite fast, but the largest challenge both for the speech language therapist and the patient is to transfer this volume into their everyday spontaneous speech. Through therapy and the everyday tasks that they are asked to do even after the end of their treatment, the patients get used to their newly acquired loud speech and begin to use it in their daily lives.
Keywords: glasbena terapija; glasen govor; hipokentična dizartrija; hypokinetic dysarthria; Lee Silverman Voice Treatment; loud speech; LSVT; Music Therapy; Parkinson Disease; Parkinsonova bolezen; Parkinson's disease; rehabilitation; therapeutic use